(untitled) (Laisvalaikio tyrimai, 2018)
Relevance of the research. The computer has long been not a luxury product; it is now common for each home to have at least one, if not several. Previously, most affordable computer was fixed, now people move much and want to keep the computer next to them, thus choosing a laptop. Because of their mobility and compactness, currently laptops are particularly popular among students. They can bring them to lectures, the university library. Business people also appreciate notebook mobility as a means of always relevant information, e-mail, and other data at hand. This is one of the main arguments that determine the choice of a laptop computer. This trend is confirmed by computer purchase BIGBANK data (2012), the users tend to buy laptops (31%), and half of them desktop computers (15%). However, R. Tiwari and S. Buse (2006) suggets that not all mobile devices provide access to mobile telecommunication networks. Standard laptops, despite their mobile devices, are often connected to the fixed network or restricted in size, weight and other factors. Laptops are used for optimized microarchitecture, characterized by higher productivity and lower energy consumption, increased working hours, compared to standard systems. The research problem is posed by the question: what factors influence the standard laptop purchase. Research object: factors affecting the standard laptop purchase in Lithuania. Research purpose was to analyse factors affecting the standard laptop purchase. Objectives to achieve the purpose: 1. Perform the statistical analysis of factors influencing the purchase of standard laptops. 2. Develop and analyse binary logistic regression model. Research methods: statistical analysis of the data and binary logistic regression analysis using a statistical package SPSS, scientific literature analysis and synthesis, induction, analogy, questionnaire (survey). Results and conclusions. Statistically insignificant factors were age, sex, social status members (students, workers, pensioners, unemployed). Adjusted binary (binomial) improved logistic regression model was suitable for the data. It was identified that 68.3% of the respondents who bought a standard laptop, and 79.7% of the respondents did not important, which computer would be chosen. The percentage of generally classified cases is 75.0%. Wald test shows that all the factors enhanced the model statistically significantly. According to the research results there is probability that the respondents with managerial status often buy standard laptops than respondents with other social status. Keywords: laptops, purchase, binary logistics regression